Gender Wage Gap Trends in Europe: The Role of Occupational Allocation and Skill Prices - Ezgi Kaya (Cardiff University, Cardiff Business School, 2014)
In this paper, we explore the recent gender wage gap trends in a sample of European countries with a new approach that uses the direct measures of skill requirements of jobs held by men and women. We find that, during the 1990s and 2000s, the gender wage gap declined in the majority of the European countries. Similar to the U.S. experience, a part of this decline is explained by changes in returns to brain and brawn skills in Austria and in the U.K. However, in contrast to the U.S. experience, the changes in returns to brain and brawn skills had a widening effect on the gender wage gap in Southern European countries and in Ireland?. Furthermore, we find that a substantial part of the changes in the gender wage gaps in European countries and in the U.S. cannot be explained by the changes in brain and brawn skill prices. The findings of this study suggest the importance of changes in labor market institutions in explaining the gender wage gap trends.
Keywords: J16; J24; J31; J71; 330; Gender wage gap; brain skills; brawn skills; decomposition